2002
DOI: 10.1029/2001rs002520
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous estimation of plasmasphere content using GPS measurements

Abstract: [1] The plasmasphere (also denoted as the protonosphere) is a large toroidal domain of light ionized particles situated above the ionosphere and confined by the Earth's magnetic field. While plasmaspheric charge densities are considerably less than those of the ionosphere, the large extent of the plasmasphere can produce significant charge column densities, or total electron content (TEC), for lines-of-sight passing through the plasmasphere. A method for Self-Calibration of Range Errors (SCORE) has been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 3 publications
3
34
0
Order By: Relevance
“…There are several studies investigating the plasmasphere using GPS data (e.g., Ciraolo and Spalla, 1997;Lunt et al, 1999c, d;Kelly, 1999;Mazzella et al, 2002;Otsuka et al, 2002;Belehaki et al, 2004;Carpenter, 2004;Izengaw et al, 2008;Manju et al, 2008;Carrano et al, 2008). Lunt et al (1999a) used model simulations to estimate the plasmaspheric electron content (PEC) at European and American mid-latitude sites for quiet magnetic conditions, at both solar maximum and minimum.…”
Section: Introductionmentioning
confidence: 98%
“…There are several studies investigating the plasmasphere using GPS data (e.g., Ciraolo and Spalla, 1997;Lunt et al, 1999c, d;Kelly, 1999;Mazzella et al, 2002;Otsuka et al, 2002;Belehaki et al, 2004;Carpenter, 2004;Izengaw et al, 2008;Manju et al, 2008;Carrano et al, 2008). Lunt et al (1999a) used model simulations to estimate the plasmaspheric electron content (PEC) at European and American mid-latitude sites for quiet magnetic conditions, at both solar maximum and minimum.…”
Section: Introductionmentioning
confidence: 98%
“…This leaves operators of middle-and low-latitude stations with a significant challenge in their bias estimation, as pTEC can exceed 10 TECU at those locations [Lunt et al, 1999a;Mazzella, 2009]. Jan, 2009Jan, 2010Jan, 2011Jan, 2012Jan, 2013 Date 30 This mechanism has been extensively researched in the works of Lunt et al [1999aLunt et al [ , 1999b, Mazzella et al [2002], and Mazzella [2009]. While this is a significant concern for midlatitude observations, the absence of an appreciable plasmasphere in the polar cap region [Lunt et al, 1999a;Nsumei et al, 2008] debunks this as a mechanism through which the observed biases, and thus the ISR-GPS comparisons, should vary at the Resolute site.…”
Section: Plasmaspheric Electron Contentmentioning
confidence: 99%
“…The daytime plasmasphere contribution to GPS-TEC is approximately ten percent, but increases to 20%-35% at night (Webb and Essex, 1997). Plasmaspheric TEC separated from GPS-TEC supplies a novel means of investigating plasmaspheric charged densities evolution and dynamics Mazzella et al, 2002;Belehaki and Jakowski, 2003). In the Grahamstown comparison, the MIDAS and ASHA solutions tracked the double peak better than the GIM (Fig.…”
Section: Discussionmentioning
confidence: 99%